Design and Experiment of Multi-information Collection System for Grain Combine Harvesters. Issue 17 (2018) - Yin, Yanxin; Zhang, Yawei; Meng, Zhijun; Du, Chen; Qin, Wuchang; Guo, Shuxia
Abstract: To obtain the online multi-information of the machine performance, working condition and other parameters for gain combine harvester, a controller area network (CAN bus) based distributed data collection, transmission and processing system was constructed and tested. In this system a series of sensors was designed or optimized, such as attitude sensors for sensing the rise and fall of header, torque sensors and revolution speed sensors for measuring the power output, torque and rotational speed, GPS module for detecting operating speed and location. And with ARM embedded processor, a universal information acquisition node was designed based on CAN bus to collect and process the datas from system-wide sensors. Furthermore, with CAN network, 3G networks and RS232-based telematics data exchange gateway, the telematics data exchange gateway was built for asynchronous communication with CAN bus node, telematics monitor, and remote database server. In addition, a order-driven synchronous data acquisition strategy was prosposed for the purpose of improving the synchronicity of combine harvester multi-information for a period of time. This system was proved to be stable, reliable, strong anti-interference and realized the object of synchronous acquisition of machine performance, working condition, power consumption and other information, and transmission frequency can reach 5KHz under 10 nodes and frame loss rate (FLR) was lower than 1%. The use of this system will be an effective support for multi-information collection of gain combine harvester.